2017
DOI: 10.1099/mic.0.000420
|View full text |Cite
|
Sign up to set email alerts
|

Viscosity-dependent variations in the cell shape and swimming manner of Leptospira

Abstract: Spirochaetes are spiral or flat-wave-shaped Gram-negative bacteria that have periplasmic flagella between the peptidoglycan layer and outer membrane. Rotation of the periplasmic flagella transforms the cell body shape periodically, allowing the cell to swim in aqueous environments. Because the virulence of motility-deficient mutants of pathogenic species is drastically attenuated, motility is thought to be an essential virulence factor in spirochaetes. However, it remains unknown how motility practically contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 29 publications
0
49
1
Order By: Relevance
“…The main cause to increase the flagella switching frequency (CCW to CW) is the chemotaxis signalling pathway, and several components of this pathway showed increased biosynthesis at 4°C. In the pathway, stimulation of the chemotaxis receptors, also known as MCPs, is followed by phosphorylation or acetylation of the response regulator CheY; phosphorylated (CheY‐P) or acetylated (CheY‐Asc); CheY then associates with the rotor of the flagella motor, and the motor changes direction to CW (Porter et al ., ; Takabe et al ., ). Six MCPs showed increased biosynthesis (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…The main cause to increase the flagella switching frequency (CCW to CW) is the chemotaxis signalling pathway, and several components of this pathway showed increased biosynthesis at 4°C. In the pathway, stimulation of the chemotaxis receptors, also known as MCPs, is followed by phosphorylation or acetylation of the response regulator CheY; phosphorylated (CheY‐P) or acetylated (CheY‐Asc); CheY then associates with the rotor of the flagella motor, and the motor changes direction to CW (Porter et al ., ; Takabe et al ., ). Six MCPs showed increased biosynthesis (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Enhancement of swimming reversal has been observed in polymer solutions, where the entire spirochetal body was exposed to changes in environmental viscosity or viscoelasticity 12 . However, we showed that swimming reversal is increased by that very limited part of the cell body is placed in viscoelastic milieu.…”
Section: Discussionmentioning
confidence: 99%
“…1B), and the morphology of the cell ends changes between spiral and hook shapes frequently: An asymmetric configuration showing spiral and hook shapes at the anterior and posterior cell ends, respectively, propels the cell unidirectionally ( Fig. 1B) [10][11][12][13] . As with other motile species, the motility of Leptospira spp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…is distinguished from the other two spirochetes by a small cell width and short wavelength [4,10]. The protoplasmic cylinder of Leptospira (Figure 1b and c) is relatively rigid, maintaining the helix parameters even during swimming, whereas both ends of the cell body are frequently transformed, as described later [11][12][13][14]. Unlike Borrelia and Brachyspira, PFs of Leptospira are too short to overlap [15].…”
Section: Cell Structurementioning
confidence: 91%